Estudio de factibilidad para la creación de una empresa productora y comercializadora de ropa para bebé en la ciudad de Bogotá D. C. (2016)
This study evaluates the feasibility to determine the feasibility of creating a marketer and producer of baby clothing company in Bogotá D.C; It begins with the diagnosis of sector analysis focused on macro and micro enterprise in the garment sector, then it proceeds to conduct a market research for the purpose of segmenting and thus able to make a planning, Finally the projection of demand and supply was made in order to design a marketing strategy for entering product thereto, further the approach of the strategies of the company to hit the market was held, resulting in the target location Negative which it is expected to distribute the product to the segment of children aged 0 to 4 years in layers 3 and 4.